2020
DOI: 10.1088/1742-6596/1525/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Using Continous Deployment techniques to manage software change at a WLCG Tier-2

Abstract: Continuous Integration (CI) and Continuous Development (CD) are common techniques in software development. Continuous Integration is the practice of bringing together code from multiple developers into a single repository, while Continuous Development is the process by which new releases are automatically created and tested. CI/CD pipelines are available in popular automation tools such as GitLab, and act to enhance and accelerate the software development process. Continuous Deployment, in which automation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Grid middleware communities have been gradually adopting cloud-native technologies for the development and deployment across WLCG data centres. For instance, (Roy et al, 2020) demonstrated the management burden is reduced and uptime has increased by adopting cloud-native technologies such as containerisation and container orchestration systems. This work has similarities to our approach for adopting standard CI/CD tools.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Grid middleware communities have been gradually adopting cloud-native technologies for the development and deployment across WLCG data centres. For instance, (Roy et al, 2020) demonstrated the management burden is reduced and uptime has increased by adopting cloud-native technologies such as containerisation and container orchestration systems. This work has similarities to our approach for adopting standard CI/CD tools.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have demonstrated that the middleware for virtualised computing and storage stacks aren’t interoperable with classic, Petascale supercomputing systems (De et al, 2021) (Boccali et al 2021). The middleware has been partially containerised (Roy et al, 2020). Our vCluster approach maps the entire middleware using three compute and storage management solutions, namely, Slurm, Kuberntes and Ceph (on-premise software-defined storage for HTC-friendly data services) (Ceph).…”
Section: Wlcg Platform Vclusters On Alpsmentioning
confidence: 99%